Reply to 'Tandem organic solar cells revisited' - Timmreck, R; Meyer, T; Gilot, J; Seifert, H; Mueller, T; Furlan, A; Wienk, M; Wynands, D; Hohl-Ebinger, J; Warta, W; Janssen, R; Riede, M; et al. (Nature Publishing Group, 2016)
Timmreck et al. reply to Bahro et al. (Nature Photon. 10, 354–355; 2016) RE: Correspondence (Nature Photon. 9, 478–479; 2015).